Analisis kemampuan representasi matematis siswa smp ditinjau dari kecerdasan logis matematis - Mutianah, Mutianah; Indiati, Intan; Endahwuri, Dhian (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2021)
This research is a descriptive qualitative research that aims to determine the mathematical representation ability of junior high school students in terms of mathematical logical intelligence. The research subjects were 3 grade VIII students of SMP Purnama 3 Semarang, each representing the categories of high, medium and low mathematical logical intelligence. The main instruments in this study were the researchers themselves and the assistive instruments used were tests and interviews. Data collection techniques using tests and interviews. The data analysis technique used was data reduction, data presentation and drawing conclusions. The technique of checking the validity of the data used triangulation methods, namely by comparing the results of the mathematical representation test with the results of the interviews. The results showed: (1) students who have high mathematical logical intelligence can use all indicators of mathematical representations maximally, (2) students who have moderate mathematical logical intelligence can use all indicators of mathematical representation but are not maximized, and (3) students who have Low mathematical logical intelligence has not been able to use all indicators of mathematical representations.